A combined experience and model based design methodology of a fuzzy control system for mean arterial pressure and cardiac output - Boldișor, Cristian Nicolae; Comnac, Vasile; Coman, Simona; Grigorescu, Sorin (IFAC Proceedings Volumes, 2011)
The control of physiological variables presents specific challenges, mainly due to the highly nonlinear, complex behavior of biological systems. Cardiovascular system stands as a clear example, with critical situations when control is desirable, but troublesome in the same time. This paper presents a fuzzy control system for two cardiovascular variables, blood pressure and cardiac output, through automatically infusion of two commonly used drugs, Sodium Nitroprusside and Dopamine, respectively. Simulations are possible, making use of a combined cardiovascular-pharmacological model, describing the effects of drugs’ infusion rates on controlled variables. The fuzzy controllers used are PI type, designed by experience, and further tuned based on the nominal values of parameters of the cardiovascular-pharmacological model. The main goal is achieving the normal values of cardiovascular variables within a reasonable time period.